Native versus non-native Prosopis woody species: Which fertilize the soil better? - Moslehi Maryam; Ahmadi Farzad; Matinizadeh Mohammad; Sadeghi Seyed Mousa; Izadi Masoumeh; Faunae Nafiseh; Alizadeh Tahereh; Shackleton Ross T. (Folia Oecologica)
This study assessed differences in the physical, chemical, and microbial properties of soils under trees of the native species Prosopis cineraria and the invasive species Prosopis juliflora trees, focusing on implications for ecosystem management and restoration. At the start of the growing season, 30 trees of each species with a trunk diameter of 15–30 cm were randomly selected. Soil samples were taken from the top 20 cm of soil profiles east of each tree, under the tree crowns and from control plots in open areas. Three soil samples per site were pooled for chemical and microbial analysis. Soil moisture was highest under P. cineraria (14.64 ± 0.3) and lowest in control plots (9.04 ± 0.65). Soil pH was highest in control soils (7.91 ± 0.09), slightly lower under P. cineraria (7.77 ± 0.06), and lowest under P. juliflora (7.49 ± 0.0). Electrical conductivity, soil salinity was highest under P. juliflora (2.25 ± 0.12). Microbial activity indicators (basal respiration and microbial biomass carbon) were greater under P. cineraria than under P. juliflora trees. Native P. cineraria trees enhance soil conditions, benefiting ecosystem management. In contrast, invasive P. juliflora trees raise soil salinity, threatening soil quality, biodiversity, and ecosystem services in the Sahara-Sahel region. Managing the spread of P. juliflora is crucial to maintaining ecosystem functions.